TEATER RAKYAT SEBAGAI MEDIA KRITIK SOSIAL: FUNGSI HUMOR DALAM SENI PERTUNJUKAN LENONG BETAWI - Julianto Ibrahim (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
Lenong Betawi is a part of community theatrical performance that is still able to survive in today globalization era. Lenong Betawi has a great role in making criticism about current social life. The criticisms are expressed through humor that is the a main characteristic of the performance art. In Betawi society, humor is a form of expression of long time under-pressured condition. The story of lenong that describes life in the colonial era has function as medium relating the past and today. The past that placed Betawi society as peripheral society is understood by lenong performers and its supporters that live in peripheral society. Community theatrical performance is part of peripheral culture, so it has interest in expressing criticism as a form of counter culture over excessive ruler domination.